The effects of different daily irradiance profiles on Arabidopsis growth, with special attention to the role of PsbS - Schiphorst, Christo; Koeman, Cas; Caracciolo, Ludovico; Staring, Koen; Theeuwen, Tom P. J. M.; Driever, Steven M.; Harbinson, Jeremy; Wientjes, Emilie (Frontiers in Plant Science, 2023)
In nature, light is never constant, while in the controlled environments used for vertical farming, in vitro propagation, or plant production for scientific research, light intensity is often kept constant during the photoperiod. To investigate the effects on plant growth of varying irradiance during the photoperiod, we grew Arabidopsis thaliana under three irradiance profiles: a square-wave profile, a parabolic profile with gradually increasing and subsequently decreasing irradiance, and a regime comprised of rapid fluctuations in irradiance. The daily integral of irradiance was the same for all three treatments. Leaf area, plant growth rate, and biomass at time of harvest were compared. Plants grown under the parabolic profile had the highest growth rate and biomass. This could be explained by a higher average light-use efficiency for carbon dioxide fixation. Furthermore, we compared the growth of wild type plants with that of the PsbS-deficient mutant npq4. PsbS triggers the fast non-photochemical quenching process (qE) that protects PSII from photodamage during sudden increases in irradiance. Based mainly on field and greenhouse experiments, the current consensus is that npq4 mutants grow more slowly in fluctuating light. However, our data show that this is not the case for several forms of fluctuating light conditions under otherwise identical controlled-climate room conditions.